[3h] thymidine uptake by the epididymis, seminal vesicles and prostate gland during postnatal development of the rat - S. Sujarit (2018)
The uptake of [3H]thymidine by the epididymis, ventral prostate gland and seminal vesicles was determined in vivo for rats aged 15, 20, 25, 30, 35, 45 and 55 days. The pattern of uptake varied considerably between organs and generally was different from patterns of growth measured as mass or ratio of mass of DNA: tissue. The ‘initial segment’ of the epididymis and caput and corpus epididymidis showed a similar pattern of [3H]thymidine uptake, being greatest in 15-day-old animals and declining thereafter. On Day 15 the cauda epididymidis had a lower uptake than more proximal regions of the epididymis, but it subsequently showed two significant peaks of increased uptake on Days 25-30 and Day 45. The uptake by the seminal vesicles was high on Day 15, fell to low levels on Day 20, increased considerably from Days 20 to 35, then gradually decreased from Day 35 to 55. The uptake by the prostate gland was a little lower than by the seminal vesicles on Days 15 and 20, then reduced to about the same level as non-reproductive tissues. © CSIRO 1991.